(untitled) (Fiep Bulletin - online, 2015)
The aim of this study was to compare the effect of two different intervals between tests in the one-repetition maximum (1 RM) performance in the bench press. The sample was composed by 19 male individuals with mean values of age, body mass, height, training experience and training frequency of 23,1 (+ 3,4) years, 76,3 (+ 9,8) kg, 178,1 (+ 8,0) cm, 34,4 (+ 23,3) months and 4,0 (+ 1,2) times a week, respectively. The volunteers were submitted to three 1 RM tests (Tests 1, 2 and 3) in two different days. In the first day, Tests 1 and 2 were carried out. They were separated by a one-hour interval, when no physical activity was allowed. Test 3 was executed at least 48 hours after Test 1. Mean values of 91,16 (+ 10,80) kg, 89,05 (+ 9,85) kg and 90,21 (+ 11,56) kg were obtained in Tests 1, 2 and 3, respectively. The difference between mean values were detected by using the one way ANOVA with repeated measures and the method of contrasts indicated significant differences (p<0,05) only between Tests 1 and 2. Thus, it can be concluded that a one-hour recovery does not allow individuals trained in resistance training to keep their performance in the 1 RM test in the guided bench press and that a 48-hours interval between tests is enough for the volunteers to obtain the same performance than that of the initial test.